Thin Film Optical Parameters Determination by the Dynamical Modelling and Stochastic Optimization Method - Stanislav Jurecka; Jarmila Mullerova (Communications - Scientific letters of the University of Zilina, 2006)
We report on a new method of experimental data processing to obtain optical parameters of thin films. Dynamical modelling of the spectral reflectance can be performed interactively in a graphical environment by the genetic search in wide interval of parameter space and then refined by the genetic algorithm method, by the Nelder-Mead downhill simplex method or Marquardt-Levenberg method. Optical parameters of hydrogenated amorphous silicon (a-Si:H) thin film used in solar cell technology are determined by this new method. The spectral reflectance is a function of optical properties and the thickness of the film. Optical parameters found by our approach do not depend on the initial spectral reflectance estimation.